2009
DOI: 10.1152/jn.91182.2008
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rostral Solitary Tract Nucleus Neurons With Identified Afferent Connections That Project to the Parabrachial Nucleus in Rats

Abstract: Suwabe T, Bradley RM. Characteristics of rostral solitary tract nucleus neurons with identified afferent connections that project to the parabrachial nucleus in rats. J Neurophysiol 102: 546 -555, 2009. First published May 13, 2009 doi:10.1152/jn.91182.2008. Afferent information derived from oral chemoreceptors is transmitted to second-order neurons in the rostral solitary tract nucleus (rNST) and then relayed to other CNS locations responsible for complex sensory and motor behaviors. Here we investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 60 publications
2
25
1
Order By: Relevance
“…The I KA influences the repetitive firing pattern of adult rNST neurons (Suwabe and Bradley 2009;Tell and Bradley 1994;Uteshev and Smith 2006). We determined prenatal development of I KA in rNST neurons using voltage protocols and 4-AP blocking.…”
Section: Resultsmentioning
confidence: 99%
“…The I KA influences the repetitive firing pattern of adult rNST neurons (Suwabe and Bradley 2009;Tell and Bradley 1994;Uteshev and Smith 2006). We determined prenatal development of I KA in rNST neurons using voltage protocols and 4-AP blocking.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their membrane characteristics, anterior Sol cells come in two varieties also in a roughly 70/30 ratio (Bradley and Sweazey, 1990). Current injection studies reveal four different characteristic patterns in anterior Sol neurons, but apparently they do not correlate with cell morphology (Bradley and Sweazey, 1992;Suwabe and Bradley, 2009). Except for the fact that more of the larger cells are located ventrally, the differentiation based on nuclear characteristics does not obviously match the cytoarchitectonic subdivisions.…”
Section: Nucleus Of the Solitary Tractmentioning
confidence: 87%
“…The rostrocentral subdivision and its caudal extension receive most of the primary afferent terminations from the chorda tympani and glossopharyngeal nerves, and provide most of the efferent projections to the parabrachial nuclei (Whitehead, 1990;Suwabe and Bradley, 2009). The rostrolateral subdivision receives sensory terminations primarily from the lingual nerve; the other three areas get little peripheral input at all.…”
Section: Nucleus Of the Solitary Tractmentioning
confidence: 99%
“…It is perhaps significant that the M-current is augmented by somatostatin (Moore et al 1988), which we have shown to be present in fibers throughout the rNST. The initial burst neurons would initiate brief inhibitory activity and therefore potentially hyperpolarize the second-order rNST neurons activating the A-current that many of these neurons express (Suwabe and Bradley 2009;Tell and Bradley 1994;Uteshev and Smith 2006). Thus the burst neurons would play an important role in sensory processing by changing the afferent excitatory response in secondorder rNST neurons.…”
Section: Repetitive Firing Patterns and Membrane Propertiesmentioning
confidence: 99%